2005
DOI: 10.1016/j.orthres.2004.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Intrajoint comparisons of gene expression patterns in human osteoarthritis suggest a change in chondrocyte phenotype

Abstract: Osteoarthritis (OA) is a degenerative cartilage disease with varying degrees of severity within a given joint. The purpose of this study was to define a sampling procedure for comparing human minimal and advanced OA cartilage in the same patient and to determine basic patterns of gene expression in these regions. A specific hypothesis under study was that the expression level of Bcl-2 would correlate with sox9 and aggrecan mRNA expression in vivo as has been demonstrated in vitro. Femoral condylar advanced OA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
74
0
1

Year Published

2006
2006
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(81 citation statements)
references
References 54 publications
6
74
0
1
Order By: Relevance
“…We assessed the microarray data for genes that in previous studies were shown to be differentially expressed in intact versus damaged regions of OA cartilage from the same joint or in normal versus OA cartilage from different patients (4)(5)(6)(7)14,(34)(35)(36)(37)(38). The name and symbol of the reported genes are shown in Table 3.…”
Section: Results Of Real-time Quantitative Pcr Of Selected 8 Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…We assessed the microarray data for genes that in previous studies were shown to be differentially expressed in intact versus damaged regions of OA cartilage from the same joint or in normal versus OA cartilage from different patients (4)(5)(6)(7)14,(34)(35)(36)(37)(38). The name and symbol of the reported genes are shown in Table 3.…”
Section: Results Of Real-time Quantitative Pcr Of Selected 8 Genesmentioning
confidence: 99%
“…Therefore, changes in the gene expression patterns of chondrocytes in response to various exogenous stimuli could affect the integrity of articular cartilage. Based on this concept, many groups of investigators have reported that gene expression in certain molecules differ from region to region within a single OA joint (4)(5)(6)(7).…”
mentioning
confidence: 99%
“…Scoring criteria were based on Yagi et al (2005). Statistics were calculated using the Mann-Whitney independent samples test, with p value less than 0.05 considered significant.…”
Section: Scoring Of Cartilage Samplesmentioning
confidence: 99%
“…Using our previously published model system utilizing intra-joint comparisons to represent minimal and advanced stages in the morphological progression of OA (Yagi et al 2005), we examined specific cellular and matrix changes associated with human OA. Our results demonstrate an upregulation of grp78 associated with human OA, suggesting that chondrocytes are experiencing altered ER function.…”
mentioning
confidence: 99%
“…As chondrocyte expression in known to undergo change with the degeneration of articular cartilage, the impact of osteoarthritis in donor cartilage on ACI is also poorly researched in the literature. 15,16 Hence, the objective of this study was to compare the gene expression profiles of OA human cartilage tissue and cultured chondrocytes, and to investigate the effect of increasing passage on the expression of chondrogenic genes in cultured human chondrocytes. The expression patterns of matrix proteins, matrix proteases, protease inhibitors, transcription factors, cytokine/growth factors, and intercellular signaling factors in human articular cartilage and isolated chondrocytes were determined by real-time polymerase chain reaction (PCR).…”
mentioning
confidence: 99%